A adesão ao novo mercado e a geração de valor às organizações - Azevedo, Regina Aparecida da Silva de (2007)
The Proposal of this study is to verify if the adherence to the New Market of BOVESPA and the adoption of the best practices of Corporate Governance, added value to the organizations. It was decided for a comparative study, analyzing the results of the economic, financial and market indicators of seven companies which pertain to the New Market. Two periods of time were defined to the analysis, where the first one considered as the period before New Market and Corporate Governance refers to the years from 1998 to 2001 and the second period limited from 2002 to 2006. The companies selection was done through the BOVESPA homepage and the indicators results were extracted from the Economatica system for the periods defined. The results of the analysis shows that the value of those companies increased in the second period, defined as the period after New Market and Corporate Governance. These results could be related to the adoption of best practices of corporate governance and with the results of IGC created by BOVESPA to measure the companies in the differentiated levels and New Market of BOVESPA, which presents the percentage of 73,92% since January 2006, compared to 63,33% of IBOVESPA which measure others companies pertained to the traditional market of BOVESPA.